HAK KEWARISAN BAGI AHLI WARIS YANG MELAKUKAN OPERASI PENYESUAIAN KELAMIN GANDA (KHUNTSA) DALAM TINJAUAN HUKUM ISLAM - Wiwit Widya Wirawati; Abdullah Kelib (Universitas Semarang, 2017)
ABSTRACTAllah SWT has set the rules on the issue of inheritance clearly and firmly in Al-Qur'an Surah An-Nisa article 11. It explains about the division of inheritance based on male and female sex, that is 2:1 (Das Sollen). But in fact there is a group of people called Khuntsa (double sex). Neither in Al-Qur‘an nor Hadist explains the provisions of inheritance for khuntsa heirs and the large number of parts they receive (Das Sein). The formulation of the problem in this study is how inheritance for the heirs who perform double genital surgery (khuntsa) according to KHI and how the right should be given to the heirs who performdouble genital adjustment surgery (khuntsa) in accordance with Islamic Law. This research uses juridical normative approach method with analytical descriptive research specification. Sources and types of data are secondary data obtained from Islamic legal norms on inheritance and khuntsa obtained from Al-Quran, Hadist, KHI, and fuqaha and experts opinions in various literature on inheritance and khuntsa. Based on the research result, khuntsa inheritance right is not regulated in KHI.Theredore if khuntsa conducts genital adjustment surgery, and get the clarity of its legal status hence its right of inheritance is as specified in Article 176 KHI. The provision of inheritance for khuntsa heirs in Islamic Law is khuntsa first predicted as male then female.Khuntsa and other heirs share the smallest and most convincing estimates, while the remaining doubts are held until the status of the khuntsa law is clear. If the khuntsa matter is clear, the acceptance of all the heirs is perfected by adding share to those who are reduced according to the acceptance they should receive. In the future, the formulation of KHI should regulate the right of khuntsa inheritance along with the amount of the inheritance received.